Advantages and disadvantages of group work on the improvement of reading skills. - Macías Silvestre, Luis Angel (2024)
This thesis explored the advantages and disadvantages of using group work to improve reading skills among primary school students. The study employed a qualitative methodology, utilizing face-to-face interviews with teachers to investigate this approach. The findings indicated that group work can foster collaborative learning, encourage active engagement, and develop essential social skills. However, the research also identified potential drawbacks, such as uneven participation, social loafing, and the risk of reinforcing weaker reading abilities within the group. The thesis concluded that group work can be an effective instructional strategy for enhancing reading skills, but it requires careful planning and facilitation by teachers. Finally, key recommendations included providing clear guidelines, assigning specific roles, monitoring group dynamics, adapting groups based on reading ability levels, offering continuous support and feedback, and cultivating metacognitive strategies. The study underscored the need for a balanced approach that maximizes the benefits of collaborative learning while mitigating the challenges. Further research is necessary to explore the long-term impacts and optimal implementation approaches for different age groups and reading proficiency levels.